LEADERSHIP OF VILLAGE CHAIRMAN DURING THE COVID-19 PANDEMIC PERIOD IN JELGUNG VILLAGE, ROBATAL DISTRICT, SAMPANG DISTRICT - Endik Hidayat (Jurnal Penelitian Administrasi Publik, 2021)
One of the duties of the village head is to protect the safety of residents and maintain village security, especially during the COVID-19 pandemic. This article answers how the leadership of the village head in the COVID-19 emergency response situation? More specifically, what abilities should the village head have in order for village government to run effectively in dealing with the threat of the spread of the corona virus in the village. This study uses Weber's leadership theory, because the village head is the authority of the highest formal leader in the village who acts as the protector of the village. This article uses a qualitative method with a descriptive approach, the research location is in Jelgung Village, Robatal District, Sampang Regency. Data collection techniques were carried out through interviews with key informants of the village head and village officials, and secondary data was taken from local media and documentation at the Jelgung village office. This article finds that the leadership model of the Jelgung village head during the COVID-19 emergency response was quite successful. The results of the study reveal three categories of expertise that village leaders must have in a COVID-19 pandemic situation. First, namely knowledge skills. Second, expertise in using communication technology devices. Third, expertise in providing solutions to villagers' problems.